2018
DOI: 10.15403/jgld.2014.1121.274.fcr
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Tumor Recurrence and Survival in Patients with Hepatocellular Carcinoma treated with Transarterial Chemoembolization

Abstract: Background & Aims: To evaluate the predictive factors for recurrence of the disease and overall survival(OS) after achieving complete response (CR) in patients with hepatocellular carcinoma (HCC) treated withtransarterial chemoembolization (TACE).Methods: From January 2013 to December 2017, 168 treatment-naïve patients diagnosed with HCCunderwent TACE as a first-line therapy and the gathered data was retrospectively reviewed. We determined the predictive factors for complete response (CR), for recurrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Thus, our study showed a decrease in OS associated to both parameters, which was independent of the assigned treatment. These data are in agreement with several retrospective studies that have reported this relationship [32,33] and with a recent study indicating that the presence of PVT is a predictive factor of poor survival in HCC [34].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our study showed a decrease in OS associated to both parameters, which was independent of the assigned treatment. These data are in agreement with several retrospective studies that have reported this relationship [32,33] and with a recent study indicating that the presence of PVT is a predictive factor of poor survival in HCC [34].…”
Section: Discussionsupporting
confidence: 93%
“…In the nonsurgical setting, pre‐intervention AFP levels have been shown to predict survival prognosis with locoregional therapies as well as with sorafenib, lenvatinib, regorafenib, cabozantinib and ramucirumab . Two studies evaluating radiofrequency ablation (RFA) for first‐line treatment of HCC in patients with Child‐Pugh A/B cirrhosis demonstrated 5‐year OS rates of 68% to 76% .…”
Section: Clinical Relevance Of Afp In Hccmentioning
confidence: 99%
“…Transarterial chemoembolization (TACE) is considered for intermediate-stage HCC that is not eligible for curative treatment options (1,2). Tumor size, number of tumors, α-fetoprotein (AFP) level, Child-Turcotte-Pugh score, vascular invasion and tumor response have been identified as significant factors predicting overall survival (OS) in HCC patients treated with TACE (3)(4)(5)(6). However, the identification of robust prognostic markers is required for the precise prediction of response to TACE in HCC patients.…”
mentioning
confidence: 99%